Primary focal segmental glomerulossclerosis and minimal change disease as one spectrum of disease - Then, Ru Fah; Tan, Yi Jun; Lim, Christopher Thiam Seong (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Minimal Change Disease (MCD) and Focal Segmental Glomerulosclerosis (FSGS) are common causes of nephrotic syndrome. These two conditions are similar in their presentations but differentiated via their histopathological features and responsiveness to corticosteroids. There are ongoing debates whether MCD and FSGS are at the same spectrum of disease rather than separate entities. FSGS has been postulated to be the severe end of the spectrum of MCD. We have reported a case that has primary FSGS after years of poorly controlled MCD, which supports both conditions are the same spectrum of disease.